Analysis of Digital Literacy-Based Business Development Strategy (Case Study of the Nila Sari Sejahtera Farmers Group, Pati Regency) - Rachmadi, Moch Faizal (Jurnal Penelitian Pendidikan, 2025)
The purpose of this study is to understand the implementation of business strategies and the importance of business feasibility studies. Furthermore, this study aims to determine the level of effectiveness, efficiency, productivity, and profitability of businesses, particularly in the field of saline tilapia fisheries in the digital era. Micro, Small, and Medium Enterprises (MSMEs) play a significant role and contribute to the national economy because they are labor-intensive, resilient, and competitive, especially during the monetary crisis. MSMEs are able to absorb labor and provide significant employment opportunities, thereby reducing the unemployment rate. One such MSME is the Nila Sari Sejahtera Farming Group. This Fish Farming Group specializes in cultivating saline tilapia, a leading product of Pati Regency. The members of the Fish Farming Group are local residents, and saline tilapia cultivation has become their primary livelihood. The method used in this study is descriptive qualitative with a case study technique. The results of the study show that: 1) Nila Sari Sejahtera Farming Group applies various business strategies in the fields of cultivation, production and post-harvest processing, 2) Consumer behavior in transactions in Fish Farming Group businesses is influenced by several factors including cultural, social, personal and sociological, 3) Digital literacy studies on MSME actors are the main strategy in business resilience and feasibility.